Harmony in Diversity at Poltekpar Bali: Implementation the First Principle of Pancasila - Ni Desak Made Santi Diwyarthi; I Wayan Adi Pratama (ITScience (Information Technology and Science), 2025)
Religious diversity in Indonesia represents both a strength and a challenge in fostering national unity, particularly in the context of higher education. As the world's largest archipelagic nation with six officially recognized religions, Indonesia upholds Pancasila as its foundational philosophy, with the first principle being